Plz....solve quickly......board is up...

Asked by  | 12th Mar, 2009, 11:59: AM

Expert Answer:

tsum of the zeroes is  given by

sum of the zeroes =-b/a

 and

 product of the zeroes=c/a

So, in this case,

sum of zeroes=2a=-1/3...(i)

and

 product of the zeroes==1/3

equation (i) gives you a=-1/6

substitute this value in theproduct of the zeroes equation and get b.

 

Answered by  | 12th Mar, 2009, 12:23: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.